A voz dos aposentados: um estudo sobre a viv??ncia da aposentadoria em banc??rios - Nogueira, B??rbara Lessa (2017)
The primery objective of this study is to investigate the experience of retirement experienced by retired of a banking institution. Therefore, we started from the macro aspects of retirement, exploring its etymology and attributed meanings, as well as the retirement forms existing in Brazil and its relation to aging. Using the psychoanalytic theoretical framework, we also studied the vision of work and organizations over this perspective. The research, of exploratory and qualitative nature, counted with the participation of four retired from the chosen banking institution. Socio-demographic data were collected to characterize the sample and posteriorly its was conducted a semi-structured interview with each participant. Using the discourse analysis technique, we discuss the categories seeking to understand the manifest content in the speech of the retired.